Use of cervical length, measured by transvaginal sonography at 22 to 26 weeks, as a predictor of preterm labour in twin pregnancy - Saini, Ricky; Yadav, Reena; Pathak, B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm labour and delivery contributes significantly to perinatal morbidity and mortality in twin gestation. Measurement of cervical length during antenatal period and subsequent follow up may identify women at risk for preterm labour. The purpose of this study was to determine if measurement of cervical length at 22 to 26 weeks can be used as a predictor of preterm labour in twin pregnancy. Methods: This prospective observational study was carried out in 50 women with twin gestation in a tertiary care teaching hospital. Cervical length was measured using transvaginal sonography and repeated every four weeks till delivery. Cervical length of ≤30 mm was taken as short cervix and delivery before 37 weeks was taken as preterm delivery. Results: Total of 18 out of 50 women (36%) delivered between 32 to 34 weeks, 14 out of 50 (28%) delivered between 34 to 37 weeks, 7 out of 50 (14%) delivered at less than 32 weeks. Therefore, total preterm deliveries at less than 37 weeks were 78%. Total 11 out of 50 (22%) delivered at term i.e. at more than 37weeks. In women, who had short cervical length (≤ 30 mm) at the time of presentation, 14 out of 37 (38 %) delivered between 30 to 34 weeks, 12 out of 37 (32 %) women delivered between 34 to 37 weeks, 5 out of 37 (14%) delivered at ≤ 30 weeks. Rest 6 out of 37 (16 %) delivered after 37 weeks. Conclusions: Short cervical length of ≤30 mm on transvaginal sonography at 22-26 weeks of gestation in twin pregnancy may be used as a screening tool in prediction of preterm labour in asymptomatic twin pregnancy.